Globalization: A very short introduction - Steger, B. Manfred (Oxford Oxford university press, 2003)
"Globalization" has become the buzz-word of our time. A growing number of scholars and political activists have invoked the term to describe a variety of changing economic, political, cultural, ideological, and environmental processes that are alleged to have accelerated in the last few decades. Rather than forcing such a complex social phenomenon into a single conceptual framework, Manfred Steger presents globalization in plain, readable English as a multifaceted process encompassing global, regional, and local aspects of social life. In addition to explaining the various dimensions of globalization, the author explores whether globalization should be considered a "good" or "bad" thing--a question that has been hotly debated in classrooms, boardrooms, and on the streets.